CREDIT GUARANTEES - Mavila H., Daniel (2004)
This article states that financial structuring of both a project and an enterprise is closely linked to guarantees. A guarantee colateral value and a series of managerial contracts as well as the issuing of bonds to obtain fresh resources such as titled bonds or values of agricultural products are shown.